Design, synthesis and photophysical properties of novel star-shaped truxene-based heterocycles utilizing ring-closing metathesis, Clauson–Kaas, Van Leusen and Ullmann-type reactions as key tools - Alvi, Shakeel; Ali, Rashid (Beilstein Journal of Organic Chemistry, 2021)
Design, synthesis and properties of polycyclic aromatic hydrocarbons (PAHs) has historically attracted a considerable interdisciplinary interest from both fundamental as well as applied viewpoint on account of their wonderful optoelectronic properties. The scientific interest in two-dimensional star-shaped PAHs particularly in truxene architectures arises because of their high thermal stability, exceptional solubility and ease with which they can be constructed and modified. Therefore, bearing in mind a wide range of applications of truxene and its congeners, herein we reveal three novel distinctly different routes for the generation of C3-symmetric pyrrole-based truxene architectures by means of cyclotrimerization, ring-closing metathesis (RCM), Clauson–Kaas and Ullmann-type coupling reactions as key steps. Moreover, we have also assembled some other interesting heterocyclic systems possessing oxazole, imidazole, benzimidazole, and benzoxazole in the framework of truxene. Additionally, the preliminary photophysical properties (absorption and emission) for these versatile systems has been revealed.
Keywords: Clauson–Kaas reaction; heterocycles; ring-closing metathesis; truxene; Ullmann-type coupling; Van Leusen reaction

(untitled) - Gámez-Valenzuela, S.; Echeverri, M.; Gómez-Lor, B.; Martínez, J. I.; Ruiz Delgado, M. C. (J. Mater. Chem. C, 2020)

(untitled) - Wu, J.; Pisula, W.; Müllen, K. (Chem. Rev., 2007)

(untitled) - Zhang, H.; Wu, D.; Liu, S. H.; Yin, J. (Curr. Org. Chem., 2012)

(untitled) - Alvi, S.; Ali, R. (Beilstein J. Org. Chem., 2020)

(untitled) - Goubard, F.; Dumur, F. (RSC Adv., 2015)

(untitled) - Wagay, S. A.; Rather, I. A.; Ali, R. (ChemistrySelect, 2019)

(untitled) - Shi, K.; Wang, J.-Y.; Pei, J. (Chem. Rec., 2015)

(untitled) - de Frutos, Ó.; Gómez-Lor, B.; Granier, T.; Monge, M. Á.; Gutiérrez-Puebla, E.; Echavarren, A. M. (Angew. Chem., Int. Ed., 1999)

(untitled) - Sharma, R.; Thomas, M. B.; Misra, R.; D'Souza, F. (Angew. Chem., 2019)

(untitled) - Sharma, R.; Volyniuk, D.; Popli, C.; Bezvikonnyi, O.; Grazulevicius, J. V.; Misra, R. (J. Phys. Chem. C, 2018)

(untitled) - Misra, R.; Sharma, R.; Mobin, S. M. (Dalton Trans., 2014)

(untitled) - Sharma, R.; Maragani, R.; Misra, R. (New J. Chem., 2018)

(untitled) - Such, B.; Trevethan, T.; Glatzel, T.; Kawai, S.; Zimmerli, L.; Meyer, E.; Shluger, A. L.; Amijs, C. H. M.; de Mendoza, P.; Echavarren, A. M. (ACS Nano, 2010)

(untitled) - de Frutos, Ó.; Granier, T.; Gómez-Lor, B.; Jiménez-Barbero, J.; Monge, Á.; Gutiérrez-Puebla, E.; Echavarren, A. M. (Chem. – Eur. J., 2002)

(untitled) - González-Cantalapiedra, E.; Ruiz, M.; Gómez-Lor, B.; Alonso, B.; García-Cuadrado, D.; Cárdenas, D. J.; Echavarren, A. M. (Eur. J. Org. Chem., 2005)

(untitled) - Ruiz, M.; Gómez-Lor, B.; Santos, A.; Echavarren, A. M. (Eur. J. Org. Chem., 2004)

(untitled) - Amsharov, K. Y.; Jansen, M. (J. Org. Chem., 2008)

(untitled) - Amsharov, K.; Jansen, M. (Chem. Commun., 2009)

(untitled) - Dorel, R.; Echavarren, A. M. (Acc. Chem. Res., 2019)

(untitled) - Chen, Q.-Q.; Liu, F.; Ma, Z.; Peng, B.; Wei, W.; Huang, W. (Chem. Lett., 2008)

(untitled) - Pérez, E. M.; Sierra, M.; Sánchez, L.; Torres, M. R.; Viruela, R.; Viruela, P. M.; Ortí, E.; Martín, N. (Angew. Chem., Int. Ed., 2007)

(untitled) - Kipping, F. S. (J. Chem. Soc., Trans., 1894)

(untitled) - Ali, R.; Alvi, S. (Tetrahedron, 2020)

(untitled) - Kotha, S.; Ali, R.; Panguluri, N. R.; Datta, A.; Kannaujiya, K. K. (Tetrahedron Lett., 2018)

(untitled) - Kotha, S.; Ali, R.; Panguluri, N. R.; Deb, A. C. (Indian J. Chem., 2018)

(untitled) - Kotha, S.; Meshram, M.; Chakkapalli, C. (Beilstein J. Org. Chem., 2018)

(untitled) - Kotha, S.; Kashinath, D.; Lahiri, K.; Sunoj, R. B. (Eur. J. Org. Chem., 2004)

(untitled) - Kotha, S.; Todeti, S.; Das, T.; Datta, A. (Tetrahedron Lett., 2018)

(untitled) - Pak, J.; Ali, R.; Park, J. S. (Bull. Korean Chem. Soc., 2016)

(untitled) - Fan, H.; Peng, J.; Hamann, M. T.; Hu, J.-F. (Chem. Rev., 2008)

(untitled) - Lee, J. Y.; Root, H. D.; Ali, R.; An, W.; Lynch, V. M.; Bähring, S.; Kim, I. S.; Sessler, J. L.; Park, J. S. (J. Am. Chem. Soc., 2020)

(untitled) - Rather, I. A.; Wagay, S. A.; Hasnain, M. S.; Ali, R. (RSC Adv., 2019)

(untitled) - Rather, I. A.; Wagay, S. A.; Ali, R. (Coord. Chem. Rev., 2020)

(untitled) - Kim, A.; Ali, R.; Park, S. H.; Kim, Y.-H.; Park, J. S. (Chem. Commun., 2016)

(untitled) - Dehmlow, E. V.; Kelle, T. (Synth. Commun., 1997)

(untitled) - Wang, X.; Wang, Y.; Yang, H.; Fang, H.; Chen, R.; Sun, Y.; Zheng, N.; Tan, K.; Lu, X.; Tian, Z.; Cao, X. (Nat. Commun., 2016)

(untitled) - Gómez-Lor, B.; de Frutos, Ó.; Ceballos, P. A.; Granier, T.; Echavarren, A. M. (Eur. J. Org. Chem., 2001)